Analisis Yuridis Ratio Decidendi Majelis Hakim Dalam Menjatuhkan Vonis Dalam Putusan Pengadilan Negeri Tenggarong Nomor 390/Pid.Sus/2021/Pn.Trg - Sunariyo; Yulianingrum, Aullia Vivi; Prasetyo, Bayu (UIR Press, 2022)
The illegal use of narcotics is a form of criminal behavior that can have a comprehensive and complicated impact on society. In the preamble to letter c of Law Number 35 of 2009 concerning Narcotics, it is stated that narcotics, on the one hand, are drugs or materials that are useful in the field of treatment or health services and scientific development, and on the other hand, can also cause dependence which is very detrimental if misused or used without supervision. Strict and careful. This research includes normative research in law, for normative legal research only recognizes secondary data, including primary, secondary, and tertiary legal materials. Data processing and data analysis depend on the type of data. Research on positive legal inventories, legal principles, clinical legal research, legal systematics, judicial decisions, legal history, and legal comparisons are all included in secondary data. In the Tenggarong District Court Decision Number 390/Pid.Sus/2021/PN. The Public Prosecutor charged the perpetrator, Mattaro bin Juma, with subsidiary charges, where the direct indictment is